Applying the linear pair theorem, the measure of angle TSV in the image given is: 86°.
<h3>How to Apply the Linear Pair Theorem?</h3>
Given the following angles in the image above:
Measure angle RSU = (17x - 3)°,
Measure angle UST = (6x – 1)°
To find the measure of angle TSV, we need to find the value of x in the given expressions as shown below:
m∠RSU + m∠UST = 180 degrees (linear pair]
Substitute the values
17x - 3 + 6x - 1 = 180
Solve for x
23x - 4 = 180
23x = 180 + 4
23x = 184
x = 8
m∠TSV = 180 - 2(m∠UST) [Linear Pair Theorem]
m∠TSV = 180 - 2(6x - 1)
Plug in the value of x
m∠TSV = 180 - 2(6(8) - 1)
m∠TSV = 86°
Therefore, applying the linear pair theorem, the measure of angle TSV in the image given is: 86°.
Learn more about the linear pair theorem on:
brainly.com/question/5598970
#SPJ1
Answer:
1.) m= — 25/21 2.) m = 0 3.) m = —1/32
Step-by-step explanation:
Answer: The final number is 5
Step-by-step explanation:
Picked number: 10
STEP are all according to what you stated
10+5=15 (first sentence)
15+10=25 (second sentence)
25+5=30 (third sentence)
30÷2-10=5 (fourth sentence)
The final number is 5.
1) (f + g)(2) = 7 + 3 = 10 The answer is C
2) (f - g)(4) = 11 - 15 = -4 The answer is A
3) f(1) = 2(1) + 3 = 5 g(1) = 1² - 1 = 0 The answer is D
4) (f xg ) (1) = 7/3 The answer is B
Answer:
.. q T 0 = (q/p)a (q/p)a − (q/p)T−10 if p ≠ q and qT0 = 1 − T0/a if p = q = 1/2.
Step-by-step explanation:
Suppose that there are two different solutions, p and q, in [a, b]. Thus p =g(p) q =g(q) p ≠ q The function g(x) satisfies the hypotheses of the mean-value ... that g(p) –g(q) = (p – q) g׳(t) Because g(p) =p and g(q) = q, the left side of Eq. (1-3) may...